2020
DOI: 10.3389/fenvs.2020.00125
|View full text |Cite
|
Sign up to set email alerts
|

Car Tire Crumb Rubber: Does Leaching Produce a Toxic Chemical Cocktail in Coastal Marine Systems?

Abstract: Crumb rubber granulate (CRG) produced from end of life tires (ELTs) is commonly applied to synthetic turf pitches (STPs), playgrounds, safety surfaces and walkways. In addition to fillers, stabilizers, cross-linking agents and secondary components (e.g., pigments, oils, resins), ELTs contain a range of other organic compound and heavy metal additives. While previous environmental impact studies on CRG have focused on terrestrial soil and freshwater ecosystems, many sites applying CRG in Norway are coastal. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 38 publications
7
83
0
Order By: Relevance
“…Typically, they consist of a mixture of natural and synthetic rubbers (40-60%), fillers (20-35%), vulcanization agents (2-5%), additives (5-10%), textile and metal reinforcements (5-10%), and process oils (12-15%) [36][37][38][39][40]. Steel cords (Fe, C) are used in tyres to provide rigidity, whilst Zn is an important element used for rubber vulcanisation and typically comprises approximately 1-2% (by mass) of the tyre [5,41,42]. A recent study examining metals leaching in crumb rubber granulates from end-of-life tyres found that Zn concentrations were substantially higher than other trace metals [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, they consist of a mixture of natural and synthetic rubbers (40-60%), fillers (20-35%), vulcanization agents (2-5%), additives (5-10%), textile and metal reinforcements (5-10%), and process oils (12-15%) [36][37][38][39][40]. Steel cords (Fe, C) are used in tyres to provide rigidity, whilst Zn is an important element used for rubber vulcanisation and typically comprises approximately 1-2% (by mass) of the tyre [5,41,42]. A recent study examining metals leaching in crumb rubber granulates from end-of-life tyres found that Zn concentrations were substantially higher than other trace metals [41].…”
Section: Introductionmentioning
confidence: 99%
“…Steel cords (Fe, C) are used in tyres to provide rigidity, whilst Zn is an important element used for rubber vulcanisation and typically comprises approximately 1-2% (by mass) of the tyre [5,41,42]. A recent study examining metals leaching in crumb rubber granulates from end-of-life tyres found that Zn concentrations were substantially higher than other trace metals [41]. As a result, tyres have been predicted to be the main anthropogenic source of roadside Zn in the atmosphere, approximately 4 times that of brake wear and greater than other potential sources such as galvanised street furniture, car bodies, and engine oil [39,41,43].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, car tire leachates can have a low pH, which might increase the bioavailability of the compounds (Capolupo et al, 2020). Indeed, the leachates from car tires have been demonstrated to have detrimental effects on algae, crustaceans, mussels, zebra fish and copepods, already at relatively low concentrations (Nelson et al, 1994;Wik and Dave, 2006;Wik et al, 2009;Capolupo et al, 2020;Halsband et al, 2020).…”
Section: Toxicity Of Twp and Its Leachatesmentioning
confidence: 99%
“…TWPs contain a wide variety of chemical substances including synthetic and natural rubber polymers, fillers such as black carbon, and different types of softeners, as well as metals from brake-abrasion (Baumann and Ismeier, 1998). The most common type of RGs are made from scrap tires, and thus contain most of the same chemical substances as TWPs (https://echa.europa.eu/hot-topics/microplastics), including high amounts of bio-accessible heavy metals such as zinc (Zn), copper (Cu) and cobalt (Co) (Canepari et al, 2018;Halsband et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The polymer composition of plastic litter observed in remote regions covers mostly five polymers: polyethylene (PE), polypropylene (PP), PE terephthalate (PET), polystyrene (PS) and polyvinyl chloride (PVC). Tire--wear particles (TWP) are an additional category and consist mainly of synthetic styrene-butadiene rubber (SBR) (Kreider et al 2010;Jan Kole et al 2017;Halsband et al 2020). All of the mentioned six plastic/rubber types are known to contain a large number of additives, with PVC and TWP containing a different mix and amount of additives than the others.…”
Section: Introductionmentioning
confidence: 99%